Childhood Gender Nonconformity and Parental Maltreatment as Mediators of Sexual Orientation Disparities in Childhood Emotional and Behavioral Difficulties. - Xu, Yin; Ma, Yidan; Rahman, Qazi (Archives of Sexual Behavior, 2024)
The mechanisms underlying sexual orientation differences in psychopathology originating in childhood remain understudied since sexual orientation does not directly manifest in childhood. This study tested whether childhood gender nonconformity and parental maltreatment before age 6 years 9 months partly explained sexual orientation disparities in the developmental trajectories of emotional and behavioral difficulties from age 6 years 9 months to 11 years 8 months. The Avon Longitudinal Study of Parents and Children was used (2182 boys and 2422 girls, Mage = 15.5, 90% White). After controlling for early life factors, non-heterosexual boys and girls displayed significantly greater emotional and behavioral difficulties than their heterosexual counterparts at all three ages. There was a sex difference in the mediating effects. For girls, sexual orientation disparities in childhood emotional and behavioral difficulties were partially explained by childhood gender nonconformity. For boys, sexual orientation disparities in childhood emotional and behavioral difficulties were partially explained by a path through greater childhood gender nonconformity, leading to increased risk of being the targets of parental maltreatment. Childhood gender nonconformity, parental maltreatment, and other early life factors only partially explain sexual orientation disparities in childhood emotional and behavioral difficulties. The mediating effects of childhood gender nonconformity and parental maltreatment on the association between sexual orientation and childhood emotional and behavioral difficulties differ between the sexes.